Means to Survive Disruption: Business Model Innovation and Strategic Continuity Management? - Jukka Heikkilä; Marikka Heikkilä; Marko Niemimaa; Jonna Järveläinen (Slovenia, 2022)
Advances in Information Technology provide opportunities for totally new business. However, we are facing not only growing number of new ventures, but increasing restructuring of existing businesses. This can be perceived e.g. in shortening life-cycles of the companies. The restructuration and birth of new companies means changing or even disrupting existing businesses. Therefore, companies, regardless of their maturity, should be prepared to evaluate these threats and opportunities actively.
Against this backdrop, we suggest to combine business modelling with systematic Business Continuity Management. We discuss the two approaches and their usefulness under different circumstances and illustrate their use when implementable, rapid reaction to changes is required, such as in industry restrucutration, or business merging and reorganization. We coin this combination as Strategic Busiess Continuity Management.
The 31th Bled eConference "Digital Transformation: Meeting the Challenges"